Ethos, logos and pathos in university students’ informal requests - Ting, Su-Hie (Penerbit Universiti Kebangsaan Malaysia, 2018)
Persuasion is used in spoken and written communication to convince the audience to take appropriate actions or to support specific viewpoints. The speaker or writer may use statistics and logical arguments, emotions and their character, authority and credibility to convince the audience. The present study examined university students’ strategies of persuading their lecturer to grant their request using Aristotle’s rhetorical proofs of ethos, logos and pathos as the framework. The data were from 165 students enrolled in an English language course in a Malaysian university. They were asked to write down what they would say to persuade their lecturer to end the class early. Some students used more than one strategy, giving rise to 180 persuasion strategies in total. Analysis of their requests showed that majority of the students used one type of rhetorical appeal to persuade. Emotional appeal (pathos) was the most popular persuasion strategy accounting for over half of the persuasion strategies identified, followed closely by the rational appeal (logos). Appeal to ethos (credibility) was seldom used. Further analysis of the use of personal pronouns showed a clear difference in that selffocus is frequent in appeals to logos whereas other-focus is frequent in appeals to pathos. When students made an appeal to logos in their requests, they used the singular first person pronoun (I, my) more than the second person pronoun because they justified their request for an early class dismissal by using their heavy workload and uncomfortable physical classroom conditions. When the students made emotional appeals, the content of their persuasion revolved around their lecturer and they made frequent use of the second person pronoun. The results suggests that the students can benefit from the teaching of persuasive discourse so that they are able to use the rhetorical appeals more effectively.